Muscle mass and inspired oxygen influence oxygen extraction at maximal exercise: Role of mitochondrial oxygen affinity. (20th June 2018) - Cardinale, D. A.; Larsen, F. J.; Jensen‐Urstad, M.; Rullman, E.; Søndergaard, H.; Morales‐Alamo, D.; Ekblom, B.; Calbet, J. A. L.; Boushel, R.
Abstract: Aim: We examined the Fick components together with mitochondrial O2 affinity (p50mito ) in defining O2 extraction and O2 uptake during exercise with large and small muscle mass during normoxia (NORM) and hyperoxia (HYPER). Methods: Seven individuals performed 2 incremental exercise tests to exhaustion on a bicycle ergometer (BIKE) and 2 on a 1‐legged knee extension ergometer (KE) in NORM or HYPER. Leg blood flow and VO2 were determined by thermodilution and the Fick method. Maximal ADP‐stimulated mitochondrial respiration (OXPHOS) and p50mito were measured ex vivo in isolated mitochondria. Mitochondrial excess capacity in the leg was determined from OXPHOS in permeabilized fibres and muscle mass measured with magnetic resonance imaging in relation to peak leg O2 delivery. Results: The ex vivo p50mito increased from 0.06 ± 0.02 to 0.17 ± 0.04 kPa with varying substrate supply and O2 flux rates from 9.84 ± 2.91 to 16.34 ± 4.07 pmol O2 ·s −1 ·μg −1 respectively. O2 extraction decreased from 83% in BIKE to 67% in KE as a function of a higher O2 delivery and lower mitochondrial excess capacity. There was a significant relationship between O2 extraction and mitochondrial excess capacity and p50mito that was unrelated to blood flow and mean transit time. Conclusion: O2 extraction varies with mitochondrial respiration rate, p50mito and O2 delivery. Mitochondrial excess capacity maintains a low p50mito which enhances O2 diffusion from microvessels to mitochondria during exercise.